La efectividad de la cartilla educativa “Martin, cuento para colorear” en salud oral en niños de 6 a 11 años. (2023)
A longitudinal study was conducted with a descriptive scope using a non-probabilistic sample. 50 children were evaluated. An oral health coloring book titled "Martin, coloring story" was designed and implemented, based on the "Smiling Chameleon take care of your teeth" educational model to reinforce oral hygiene tools in children.